Effects Of A Human Agent And The Application Of The Modality Principle On The Learning Of Chinese Idioms And The Attitudes Among Students With Different Levels Of Intelligence [LB1529.5.C5 L693 2008 f rb]. - Li, Xuanxi (2008)
The purpose of this research was to investigate the impact of a Human Agent (HA)’s visual presence and the modality effect in a Computer-based learning (CBL)